PERANAN PENYULUH PERTANIAN DALAM KELOMPOK TANI DI DESA TEMBER KECAMATAN TOMPASO KABUPATEN MINAHASA - Lontoh, Gabriel Anatasia; Benu, Noortje Marsellanie; Jocom, Sherly Gladys (Sam Ratulangi University, 2022)
This study aims to examine the role of agricultural extension workers in farmer groups in Tember Village, Tompaso District, Minahasa Regency. The research was conducted from July to October 2021. The research was located in Tember Village, Tompaso Lama District, Minahasa Regency. The data used in this study are primary and secondary data. Sampling was done intentionally (purposive sampling), as many as 20 farmers from 50 farmers who are members of the Maesa farmer group. Furthermore, the data were analyzed descriptively using a Likert scale. The results showed that the role of the extension worker in the farmer group obtained from the respondents stated that the average respondent's assessment was in the role category, where the variable role of the extension worker was as a guide (76.66%), the variable of the role of the instructor as organizer and dynamist (80%) and the variable role extension workers as technical trainers (85.55%).